The Impact of Reproductive Health and Family Planning Education on Contraceptive Behavior Among Couples of Reproductive Age in Muara Enim Regency - Hasrida; Lusianah; Nia Neltaria; Rusi Hardianti; Sri Hartati; Yozi Ariza (Jurnal Penelitian Pendidikan IPA, 2025)
Health education is a promotional measure to improve public health. However, its success is also influenced by the environment and the information received by individuals. Therefore, reproductive health and family planning (FP) education plays a crucial role in influencing changes in contraceptive behavior among couples of childbearing ages. Objective: To determine the effect of reproductive health and family planning (FP) education on changes in contraceptive behavior among couples of childbearing ages in Muara Enim Regency in 2025. Method: This study used a pre-experimental method, which is a type of research designed to examine the effect of a specific treatment and evaluate its impact on other variables under controlled conditions. The sample size in this study was 250 people, and the Wilcoxon statistical analysis test was used. Results: There was an effect of reproductive health and family planning (FP) education on changes in contraceptive behavior among couples of childbearing ages, with a p-value of < 0.001. Conclusions and Recommendations: Active health education can increase knowledge about the benefits and various methods of contraception, as well as strengthen communication and collaboration in decision-making regarding contraceptive use, thereby supporting successful family planning.